Analisa Kondisi Kerusakan Jalan Desa Pante Rakyat, Kecamatan Babahrot, Kabupaten Aceh Barat Daya - Rofika, Rita; Ikhsan, Muhammad; Suciatina Silvia, Cut (Rifa'Institute, 2022)
The road is a land transportation infrastructure that is very important in smoothing the activities of other economic and social relations. But if there is damage to the road will result not only hinder other economic and social activities but can occur accidents. This study aims to find out the types of road damage, the causative factors and solutions to overcome the damage that occurs. The method used is field research with primary data in the form of survey results of road damage along 1.00 Km. The survey results of the type of road damage on STA 0 + 000 - 1 + 000 are cracked and perforated. This will result in discomfort for motorists using the road. The factors causing damage in general are increased traffic volume load, poor drainage system, poor material properties, climate, unstable soil conditions, very thin pavement layer planning, the process of carrying out work that is not in accordance with specifications. Corrective action that can be taken is corrective action for each segment.